2002
DOI: 10.1103/physrevlett.88.163202
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Positron-Atom Annihilation near the Positronium Formation Threshold

Abstract: The behavior of the positron- 2 gamma annihilation rate on an atomic target near the positronium (Ps) formation threshold is determined. When the positron energy epsilon approaches the threshold epsilon(thr) from below, the effective number of electrons contributing to the annihilation, Z(eff), grows as Z(eff) approximately A/square root of [epsilon(thr)-epsilon], where A is related to the size of the Ps formation cross section, sigma(Ps) approximately B square root of [epsilon-epsilon(thr)], by A = B square r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
27
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 16 publications
(23 reference statements)
1
27
0
Order By: Relevance
“…An application of the S-wave threshold law to Eq. (1) leads to the divergence as ÿ ÿ1=2 [7], where E ÿ E th 1s, instead of the more rapid divergence as ÿ ÿ1 expected by Laricchia and Wilkin. The recent time-dependent close-coupling calculation by Yamanaka and Kino [6] fails to reproduce this remarkable threshold increase.…”
mentioning
confidence: 81%
See 1 more Smart Citation
“…An application of the S-wave threshold law to Eq. (1) leads to the divergence as ÿ ÿ1=2 [7], where E ÿ E th 1s, instead of the more rapid divergence as ÿ ÿ1 expected by Laricchia and Wilkin. The recent time-dependent close-coupling calculation by Yamanaka and Kino [6] fails to reproduce this remarkable threshold increase.…”
mentioning
confidence: 81%
“…[10,11]. Gribakin and Ludlow [7] showed that this modification leads to the absence of any threshold divergence of an or the threshold rise of Ps ; they connect smoothly from one to the other across E th 1s.…”
mentioning
confidence: 95%
“…The features of positron annihilation cross sections (PACSs) observed for very-low energy positrons in molecular gases, on the other hand, have received thus far less attention from theory and computations (for a general discussion, see [3][4][5] and references therein). The positron scattering from molecular targets also differs considerably from the case of electrons because of the possibility of positronium (Ps) formation and of the resulting annihilation by the emission of two or three quanta.…”
mentioning
confidence: 99%
“…We use the many-particle PT, exactly the RPAE method [5,6,10]. In the lowest order in the electron interaction the amplitude of presented decay is determined by the diagrams in Fig.…”
Section: Theorymentioning
confidence: 99%
“…The summation Π includes all the projections of orbital and spin momenta of initial and final vacancies, as well as the factor F is determined as [10][11][12]:…”
Section: Theorymentioning
confidence: 99%